Association Between Environmental Factors and Oral Epstein-Barr Virus DNA Loads: A Multicenter Cross-sectional Study in China. (11th October 2018) - He, Yong-Qiao; Liao, Xiao-Yu; Xue, Wen-Qiong; Xu, Ya-Fei; Xu, Feng-Hua; Li, Fang-Fang; Li, Xi-Zhao; Zhang, Jiang-Bo; Wang, Tong-Min; Wang, Fang; Yu, Huan-Lin; Feng, Qi-Sheng; et al.
Abstract: Background: Oral Epstein-Barr virus (EBV) status reflects host EBV activity and potentially links to EBV-associated diseases, however, factors influencing oral EBV loads or reactivation, such as environmental exposures or host factors, are not fully understood. Methods: A 2-stage, multicenter, cross-sectional study of 6558 subjects from 21 administrative cities of southern China and 3 populations from representative geographical areas in China (referred to as the south, north, and northeastern populations) was performed. The relationships between demographical factors and environmental exposures to EBV loads were analyzed by logistic regression models. Results: Current smoking, with a dose-response effect, was found to be strongly associated with higher oral EBV loads in the pooled data, with an odds ratio of 1.58 (95% confidence interval, 1.39–1.79), as well as in each of the separate populations. The odds ratio increased to 3.06 when current smokers in southern China were compared to never smokers in northern China. Additionally, higher oral EBV loads tended to be detected in older participants, male participants, and participants in southern China. Conclusions: This study provided evidence linking the effect of host-environmental factors, particularly smoking, to oral EBV activity. It could strengthen our understanding of the possible causal roles of EBV-related diseases, which may help to prevent or mitigate EBV-associated diseases. Abstract : Our multicenter cross-sectional study in China provided evidence linking the effect of host-environmental factors to oral Epstein-Barr virus (EBV) activity. Higher oral EBV loads tended to be detected in smokers, older participants, male participants, and participants in southern China.